Elevation patterns of plant diversity and recent altitudinal range shifts in Sinai’s high mountain flora - Coals, Peter; Shmida, Avi; Vasl, Amiel; Mansour, Nasr; Gilbert, Francis (Wiley, 2018)
Questions: Is there evidence of recent altitudinal range shifts in a hyper-arid Middle Eastern desert mountain flora? How do the directions of shift for upper and lower altitudinal range limits of plants vary? Location: Hyper-arid mountain desert, St Katherine Protectorate, South Sinai, Egypt. Method: We tested for shifts in both upper and lower altitudinal range limits by comparing a 1970s dataset of recorded species’ limits with recent surveys using altitudinal transects across 36 sites. Altitudinal limits between 63 paired upper-limit and 22 paired lower-limit values from the 1970s and 2014 were compared using paired t-tests; binomial tests were used to indicate the dominant direction of change. The upper and lower limits of 22 species were considered together to allow assessment of overall altitudinal range-size changes. In order to avoid the potential effect of yearly environmental fluctuations on the distributions of annual species, subsets of upper and lower limit shifts were taken for perennials, and trees and shrubs. Results: Our results show significant overall upslope shifts in mean upper altitudinal limits and significant overall downslope shifts in mean lower altitudinal limits. A majority of assessed species expanded their altitudinal ranges, but the responses of individual species varied. Since perennial herbs/graminoids, and trees and shrubs, show strong patterns of change, we suggest there has been a long-term shift in altitudinal range in South Sinai’s mountain flora. Greater research effort needs to be focussed upon the drivers of range-shift responses in arid regions.